Subtle Regulation of Potato Acid Invertase Activity by a Protein Complex of Invertase, Invertase Inhibitor, and SUCROSE NONFERMENTING1-RELATED PROTEIN KINASE - Lin, Yuan; Liu, Tengfei; Liu, Jun; Liu, Xun; Ou, Yongbin; Zhang, Huiling; Li, Meng; Sonnewald, Uwe; Song, Botao; Xie, Conghua (Plant Physiology, 2015)
Slowing down cold-induced sweetening (CIS) of potato (Solanum tuberosum) tubers is of economic importance for the potato industry to ensure high-quality products. The conversion of sucrose to reducing sugars by the acid invertase StvacINV1 is thought to be critical for CIS. Identification of the specific StvacINV1 inhibitor StInvInh2B and the alpha- and beta-subunits of the interacting protein SUCROSE NONFERMENTING1-RELATED PROTEIN KINASE from the wild potato species Solanum berthaultii (SbSnRK1) has led to speculation that invertase activity may be regulated via a posttranslational mechanism that remains to be elucidated. Using bimolecular fluorescence complementation assays, this study confirmed the protein complex by pairwise interactions. In vitro kinase assays and protein phosphorylation analysis revealed that phosphorylation of SbSnRK1 alpha is causal for StvacINV1 activity and that its active form blocks the inhibition of StInvInh2B by SbSnRK1 beta, whereas its inactive form restores the function of SbSnRK1 beta that prevents StInvInh2B from repressing StvacINV1. Overexpression of SbSnRK1 alpha in CIS-sensitive potato confirmed that SbSnRK1 alpha has significant effects on acid invertase-associated sucrose degradation. A higher level of SbSnRK1 alpha expression was accompanied by elevated SbSnRK1 alpha phosphorylation, reduced acid invertase activity, a higher sucrose-hexose ratio, and improved chip color. Our results lend new insights into a subtle regulatory mode of invertase activity and provide a novel approach for potato CIS improvement.